Redescription of pupae of the New World predaceous midges, Pachyhelea pachymera (Williston, 1900) and Clastrieromyia dycei Spinelli and Grogan, 1986 (Diptera: Ceratopogonidae) - Spinelli, Gustavo Ricardo (2016)
The pupae of the predaceous midges, Pachyhelea pachymera (Williston, 1900) and Clastrieromyia dycei Spinelli and Grogan, 1986, are redescribed and illustrated using modern terminology from specimens collected in Buenos Aires and Entre Ríos Provinces, Argentina, and Artigas Department, Uruguay. Both species exhibit elongated, thin anteromedial sensilla that are characteristic of other genera in the tribe Palpomyiini. Character differences from known pupae of the New World species in the Palpomyia tibialis group are noted for P. pachymera and differences from other Palpomyiini genera are noted for C. dycei.